2022
DOI: 10.1520/gtj20210031
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Model Test of Fully Buried Portal Frame-Shaped Slope-Stabilizing Piles

Abstract: Fully buried portal frame-shaped piles have been widely used to control and stabilize large-scale landslides or slopes. However, the working mechanism of portal frame piles, such as the soil–pile interaction and load transfer behavior, is still not fully understood, which has limited the development of effective pile designs and construction. In this study, a well-designed laboratory model test was conducted in a sandy soil slope with a man-made slip surface. Nine portal frame piles were installed, synthetical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The sectional bending moment of the pile was calculated based on the data collected through strain gauges. The calculation formula can be expressed in Equation (20). The direction of the pile bending moment was defined according to the coordinate system and concerning the right-hand rule, as shown in Figure 9.…”
Section: Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sectional bending moment of the pile was calculated based on the data collected through strain gauges. The calculation formula can be expressed in Equation (20). The direction of the pile bending moment was defined according to the coordinate system and concerning the right-hand rule, as shown in Figure 9.…”
Section: Test Resultsmentioning
confidence: 99%
“…Some scholars indicated that the crown beam plays a significant role in coordinating the deformation of anti-slip piles, and the back-row piles had a greater impact on slope stability than the front-row piles [17,18]. Reliability and economic efficiency are two important factors for portal frame composite structure, and excessively large pile spacing and crown beam size leads to the failure in the slope reinforced by anti-slide piles, which may weaken the soil arching effect [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the single pile, the combination pile offers two prominent advantages (Dai et al, 2022;Xiong et al, 2022;Zhao et al, 2022).…”
Section: Improving the Applicability Of The Anti-slide Pile 2211 Comb...mentioning
confidence: 99%